TRAINING ON ENTREPRENEURSHIP SKILLS IN MARKETING PRODUCTS FOR STUDENTS AND ONLINE-BASED MSMEs - Siti Mariam; Evi Mafriningsianti; Syech Idrus; Yuliana Yuliana; Ahmad Rifa’i; Irwan Sukmawan (International Journal of Engagement and Empowerment, 2023)
Along with the development of technology and business trends that are constantly changing, an entrepreneur must keep moving and be able to adapt quickly to remain competitive and survive in an increasingly competitive market. Creativity and innovation are important keys to making the most of information technology in business. Utilization of information technology and social media can help entrepreneurs improve business efficiency and effectiveness, expand market reach, increase consumer involvement, and speed up the transaction process. Therefore, entrepreneurs need to learn and understand how to use information technology and social media properly and effectively in their business. Community service activities that focus on product marketing training through social media are very important activities to help entrepreneurs increase sales of their products. In today's digital era, marketing through social media is becoming increasingly important because many consumers actively use social media as a means to find and buy products. Through this training activity, participants are expected to be able to understand the concept of entrepreneurship and digital marketing in depth, and be able to optimize the use of social media to increase sales of their products. By understanding the characteristics of a good entrepreneur, participants will be able to increase creativity and innovation in developing their products